Time-varying Doppler analysis of electromagnetic backscattering from rotating object - Chen, V.C.; Lin, C.-T.; Pala, W.P. (2006 IEEE Conference on Radar, 2006)
Electromagnetic backscattering from rotating objects is subject to Doppler modulations that enable us to determine dynamic properties of objects and provide useful information about the objects. In this paper, we discuss how to analyze time-varying Doppler spectra, how to deal with undersampled data, and how to characterize target's dynamic motions from the time-varying Doppler spectra.